Answer:
y = –3x – 6
Explanation:
We'll begin by obtaining the slope of the equation y = –3x – 2.
This can be obtained by comparing
y = –3x – 2 with y = mx + c
Thus, the slope (m) of the equation
y = –3x – 2 is –3.
Next, we shall determine the slope of the equation parallel to line with equation y = –3x – 2.
This is illustrated below:
For parallel lines, the slope are related as follow:
m1 = m2
m1 = –3
m2 = m1 = –3.
Finally, we shall determine the equation as follow:
Coordinate = (–3, –3)
x1 coordinate = –3
y1 coordinate = –3
Slope (m) = –3
y –y1 = m(x – x1)
y – (–3) = –3 (x – (–3))
y + 3 = –3 (x + 3)
y + 3 = –3x – 3
Rearrange
y = –3x – 3 – 3
y = –3x – 6
Thus, the equation parallel to the line is y = –3x – 6